2016
DOI: 10.1089/lrb.2013.0046
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Manifestations of Senile Lymph Nodes in the Popliteal Fossa

Abstract: The radiologic manifestations of senile lymph nodes in the popliteal fossa have been presented and discussed to upgrade our radiologic and anatomical knowledge. This will be of benefit for radiologic and clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Clinical management requires accurate and detailed anatomical understanding of the lymphatic pathways in the lower limb. The knowledge of the superficial lymphatic anatomy in the lower limb has been updated during the last decade . Although the deep lymphatic pathways of the lower limb had been mentioned and depicted in few literature but the relationship between the superficial and deep lymphatic vessels of the lower limb has not yet been clarified, the knowledge is unable to explain some of the unexpected findings seen clinically .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical management requires accurate and detailed anatomical understanding of the lymphatic pathways in the lower limb. The knowledge of the superficial lymphatic anatomy in the lower limb has been updated during the last decade . Although the deep lymphatic pathways of the lower limb had been mentioned and depicted in few literature but the relationship between the superficial and deep lymphatic vessels of the lower limb has not yet been clarified, the knowledge is unable to explain some of the unexpected findings seen clinically .…”
Section: Discussionmentioning
confidence: 99%
“…It was not realized until the mid 20th century that a lymph vessel, arising from the superficial popliteal lymph node, could drain into the deep popliteal lymph node from where the efferent vessel travelled with the femoral vascular bundle and then entered the inguinal lymph node . Recently, it was found that the lymph vessel arising from the deep popliteal lymph node could drain into the inguinal lymph node via the femoral route, the external iliac node via the profunda route by piercing the obturator foramen and the inferior gluteal node via the sciatic route . In this study, we have presented two sites of the perforating lymph vessel linking the superficial posterior group to the deep lymph vessel; one was in the popliteal fossa regularly and the other one in the distal third of the leg, which, unfortunately, could be an alternative pathway for metastases disease in the leg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recalling the history of research conducted on the lymphatic system, it showed that the lymphatic anatomy of limbs was not available until the mercury infusion technique was applied [1][2][3][4]. Although the knowledge of the superficial and deep lymphatic anatomy of limbs has been updated during the last decade [5][6][7][8] the deep lymphatic anatomy of the foot remains the least described in medical literature.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical management requires accurate and detailed anatomical knowledge of the human lymphatic system. Although, the superficial and deep lymphatic anatomy in the lower limb has been updated during the last decade by using the new technique [1][2][3][4], but the deep lymphatic anatomy remained in uncertainty. Therefore, further study should be carried to renew the knowledge of the human lymphatic system to meet the needs of precise clinical management, modern education, and advanced scientific research.…”
Section: Introductionmentioning
confidence: 99%